Kinetics of methane gas hydrate formation with microscale sand in an autoclave with windows. (1st December 2017) - Wang, WuChang; Jiang, Kai; Li, YuXing; Shi, ZhengZhuo; Song, GuangChun; Duan, Ruixi
Abstract: During the exploitation of subsea natural gas hydrate (NGH) deposits, the muddy silt from marine sediment is carried by the fluid inside the wellbore. Furthermore, NGH is readily formed inside the wellbore when the fluid is in a hydrate formation area. Once NGH has formed inside the wellbore, the exploitation operation will be hindered, or shut down, due to the blockage. Understanding the kinetic characteristics and morphology of NGH formation is important to prevent its occurrence. To this end, a high-pressure autoclave system was designed and constructed in this work. Experiments were conducted to determine the mechanism of sand aggregation, the effect of sand on the kinetic characteristics and the morphology of hydrate formation. Additionally, models of hydrate particle formation with sand and sand aggregation, and structure of wall-attached hydrate layer growth were proposed. The results showed that sand could promote the growth of hydrate and the wall-attached hydrate layer. Additionally, it was observed that hydrate particles were formed with and without sand, and that the wall-attached hydrate layer presented a sandwich structure. The rolling and colliding implantations of hydrate particles were also observed experimentally. Sand aggregation was caused by hydrate particle implantation and the carrying sand effect. Hydrate particle formation with sand can be divided into four stages: nucleation, surface growth, shell formation, and shell growth. The sand aggregation process can also be divided into four stages: hydrate film formation, rupture of hydrate film, particle aggregation, and hydrate layer sintering. For structure of wall-attached hydrate layer growth, the growth front of the hydrate layer was concave-upward.